Implementasi Pendidikan Karakter Religius Melalui Kegiatan Pembiasaan Harian pada Anak Usia Dini di Yayasan Taman Pendidikan TPQ/RA Wahyu - Rizka Auliah Hasibuan (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This community outreach activity was conducted at the Wahyu TPQ/RA Foundation, focusing on the implementation of religious character education through daily habituation activities for early childhood. The main issue behind this activity is the importance of instilling religious values ​​from an early age to shape a generation with noble morals and Islamic character. The method used was a qualitative method with a participatory approach, through observation, interviews, and documentation during religious habituation activities such as prayers before and after studying, reading short surahs, practicing congregational prayers, and Friday Infaq activities. The results of the activity showed a significant increase in children's involvement in religious activities and their consistency in carrying out positive habits. Children became more accustomed to prayer, their manners improved, and an awareness of sharing emerged through infaq activities. These findings are in line with the theory of habituation (habit formation), which emphasizes repetition as a strategy for forming character. This activity contributes to the development of science in the field of early childhood education, particularly in the aspect of religious character education, and can be a model of good practice that can be replicated by similar educational institutions.